The misadventures of Nero Wolfe : parodies and pastiches featuring the great detective of West 35th Street - Stout, Rex, 1886-1975 (MysteriousPress.com/Open Road Integrated Media, 2020)
Stories that pay tribute to Rex Stout's legendary private detective by Lawrence Block, Loren D. Estleman, John Lescroart, Robert Goldsborough, and more. If imitation is the sincerest form of flattery, then Nero Wolfe and Archie Goodwin have been widely flattered almost from the moment Rex Stout first wrote about them in 1934. The Misadventures of Nero Wolfe collects two dozen literary tributes to one of crime fiction?s best-loved private detectives and his Man Friday. Included are: A 1947 pastiche by award-winning crime writer Thomas Narcejac. Rollicking new stories written especially for this collection by Michael Bracken and Robert Lopresti. Stories by bestselling authors including Lawrence Block and Loren D. Estleman. Chapters from Robert Goldsborough's authorized continuation of the Wolfe series; Marion Mainwaring's 1955 tour de force Murder in Pastiche; and John Lescroart's Rasputin's Revenge, which reimagines a young Wolfe as the son of Sherlock Holmes. Also featuring a reminiscence from Rex Stout's daughter, this is a treasury of witty and suspenseful crime writing for every fan of the portly private detective. --from amazon.com.